2015
DOI: 10.1016/j.ejvs.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential FDG-PET Uptake Patterns in Uninfected and Infected Central Prosthetic Vascular Grafts

Abstract: The patterns of FDG uptake for uninfected vascular grafts largely overlap with those of infected vascular grafts. This questions the value of these individual FDG-PET-CT parameters in identifying infected grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 17 publications
4
44
0
6
Order By: Relevance
“…A diffuse homogeneous uptake was observed in 67 grafts (63%) and heterogeneous uptake was observed in 31 grafts (29% F-FDG PET uptake in non-infected grafts is a result of a local sterile inflammatory process around the prosthesis due to a foreign body-related reaction, and also related to the type of implanted material. Moreover, Berger et al found the mentioned standard parameters largely to overlap in infected and uninfected central vascular grafts [34], which confirms our findings that conventional parameters are not sufficient in distinguishing these groups.…”
Section: Discussionsupporting
confidence: 81%
“…A diffuse homogeneous uptake was observed in 67 grafts (63%) and heterogeneous uptake was observed in 31 grafts (29% F-FDG PET uptake in non-infected grafts is a result of a local sterile inflammatory process around the prosthesis due to a foreign body-related reaction, and also related to the type of implanted material. Moreover, Berger et al found the mentioned standard parameters largely to overlap in infected and uninfected central vascular grafts [34], which confirms our findings that conventional parameters are not sufficient in distinguishing these groups.…”
Section: Discussionsupporting
confidence: 81%
“…Meanwhile, the patient with an infected graft had a peri-prosthetic SUV max of 17.1, and he eventually succumbed to sepsis. However, the accuracy of individual 18 FDG-PET/CT parameters including SUV max for separating infected and non-infected grafts has been questioned [19]. It is possible that ongoing antibiotic therapy may impair discrimination of graft infection from nonspecific uptake at PET/CT, and further prospective analysis is required.…”
Section: Fdg Uptake and Graft Infectionmentioning
confidence: 99%
“…Synthetic graft material is 18 F-FDG avid in up to 92% of non-infected patients following surgery for non-inflammatory aneurysm repair or bypass of obstructive arterial atherosclerosis [17,19,20].…”
mentioning
confidence: 99%
“…This region was the same as the echo-free space observed on thoracic echocardiography. 18 F-FDG PET/CT was very useful for the diagnosis of aortic prosthetic graft infection.However, 18 F-FDG PET/CT images do not completely discriminate between infected grafts and noninfected grafts, because these images sometimes overlap [8]. However, when 18 F-FDG PET/CT is combined with the results of the physical examination or laboratory…”
mentioning
confidence: 92%